Marine eutrophication review - Hinga, Kenneth R.; Jeon, Heeseon; Lewis, Noelle F. (NOAA Coastal Ocean Program - Decision Analysis Series No. 4, 1995)
Contents: Part I: Quantifying the effcts of nitrogen enrichment on phytoplankton in coastal ecosystems. Part II: Bibliography with abstracts.